Hubungan Pola Pemberian MP ASI Dengan Status Gizi Pada Bayi Usia 6-12 Bulan Di Wilayah Kerja Puskesmas Pataruman 1 Kota Banjar - Anggi Belia Ligiani; Diah Atmarina Yuliani (Jurnal Kebidanan Harapan Ibu Pekalongan, 2025)
Background: Appropriate complementary feeding practices are crucial factors in determining nutritional status of infants. Inappropriate complementary feeding patterns can cause nutritional problems in infants aged 6-12 months, thus evaluation of complementary feeding practices and their relationship with infant nutritional status is necessary. Objective: To determine the relationship between complementary feeding patterns and nutritional status in infants aged 6-12 months in the working area of Pataruman 1 Primary Health Center, Banjar City. Methods: This study used a cross-sectional design with a population of toddlers receiving complementary feeding at Pataruman I Primary Health Center, Banjar City based on January-February 2025 data totaling 300 people. The research sample was determined using the sample size formula for ordinal-nominal correlative analytics with a sample size of 60 infants aged 6-12 months. Results: Most complementary feeding patterns were in the appropriate category, namely 35 infants (58.3%). Most infant nutritional status was in the good nutrition category, namely 37 infants (61.7%). The analysis results showed a significant relationship between complementary feeding patterns and nutritional status with the percentage of good nutritional status reaching 85.7%. Conclusion: There is a significant relationship between complementary feeding patterns and nutritional status in infants aged 6-12 months in the working area of Pataruman 1 Primary Health Center, Banjar City.